Two-scale computation of N2–H2 jet flow based on QGD and MMD on heterogeneous multi-core hardware. (June 2018) - Kudryashova, T.; Karamzin, Yu.; Podryga, V.; Polyakov, S.
Abstract: Gas mixture flows take place in a wide range of scientific and technical problems, including space applications, microchannel streams, nanotechnology and others. This paper deals with numerical simulation of gas mixture flows in microchannels. For such flows speeds can have supersonic, subsonic and transonic ranges according to parameters of gas stream and properties. The supersonic expansion of gas mixtures is accompanied by several simultaneous nonequilibrium processes: interfusion of layers, shock waves, heat exchange with walls etc. To investigate these complex problems, it is essential to develop adequate numerical technique that contains stable and robust numerical algorithms and calculations based on fine grids. These calculations are supposed to be carried out by means of high performance computer systems. This paper presents a new method for simulating gas mixture flows that enables us to solve similar issues and reduce computing time (Garzo et al., 1989; Elizarova, 2009). Particularity of our approach is combination of continuum mechanics and Newton's dynamics models. For computer realization of the approach we use grid methods for solution of macroscopic quasigasdynamic (QGD) equations and molecular dynamics methods (MMD). Some results of numerical modelling are discussed.